1996
DOI: 10.1002/j.2161-1912.1996.tb00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Problems Caused for Mental Health Professionals Worldwide by Increasing Multicultural Populations and Proposed Solutions

Abstract: Psychiatric disorders on a global scale, combined with rapid national population diversification, demand that mental health professionals worldwide become more informed about the realities of diagnosing and treating a multicultural patient population. Recommendations are offered to enable such professionals to most efficaciously diagnose and treat patients from diverse sociocultural backgrounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Few studies, however, have examined the roles of specific ethno-cultural variables in healthcare disparities. This gap in the literature is surprising, because previous studies have shown that ethnic and cultural backgrounds influence attributions about illness etiology, help-seeking attitudes, health beliefs and behaviors, and description of symptoms (Baider & Sarell 1983; Chiu 1996). Many studies have reported significant relationships between culturally-related health beliefs and behaviors.…”
Section: Introductionmentioning
confidence: 95%
“…Few studies, however, have examined the roles of specific ethno-cultural variables in healthcare disparities. This gap in the literature is surprising, because previous studies have shown that ethnic and cultural backgrounds influence attributions about illness etiology, help-seeking attitudes, health beliefs and behaviors, and description of symptoms (Baider & Sarell 1983; Chiu 1996). Many studies have reported significant relationships between culturally-related health beliefs and behaviors.…”
Section: Introductionmentioning
confidence: 95%
“…This trend, coupled with the universality of mental health issues, increases the likelihood that counselors will diagnose and treat clients from diverse backgrounds. Clients from different cultural groups tend to express their symptomatology differently, to function differently within the counseling context, and to subscribe to different norms and beliefs about counseling interventions and treatment options (Chiu, 1996). More important, clients from ethnic minority groups tend not to use counseling services enough and to prematurely terminate counseling services at a much higher rate than do clients who are not members of ethnic minority groups (Heppner & O'Brien, 1994;Richardson & Molinaro, 1996).…”
Section: Counselor Education and Multicultural Competencies: La~1ps Tmentioning
confidence: 99%
“…Faculty development provides a mechanism for enhancing the training and clinical experience of faculty members. Prioritizing multicultural awareness training for faculty is paramount (Torres et al, 1997), because continuing education will promote increased multicultural competence for faculty members (Chiu, 1996). At the personal development level, faculty members can develop a mentortng relationship with a colleague whom the faculty member perceives as working toward multicultural competence (Arredondo et al, 1996).…”
Section: Faculty-oriented Recommendationsmentioning
confidence: 99%
“…The results of their studies indicated that African-Americans and white Americans were more likely to be diagnosed with schizophrenia, whereas Latino clients were more likely to be diagnosed as having other mental illnesses. Latino clients were also less likely to receive medication than were the other two groups (Chiu, 1996).…”
Section: Respecting Othersmentioning
confidence: 98%